A Secure Online Key Establishment Scheme for Mobile Heterogeneous Sensor Networks - Sarmad Ullah Khan; Claudio Pastrone; Luciano Lavagno; Maurizio A. Spirito (International Journal of Distributed Sensor Networks)
Advancement in wireless sensor network (WSN) technology makes it more attractive technology to be adopted in real world applications including home and industrial automation and e-health or infrastructure monitoring. However the mobility consideration in these applications makes the security requirements an essential and challenging task. To make the communication secure and the network robust against attacks, a proper key management scheme should be used. This paper presents a secure online key establishment and authentication scheme for mobility supported heterogeneous sensor networks. The performance evaluation of the proposed scheme is done using OMNET++ simulator while AVISPA tool is used to validate the security of the proposed scheme. It is clear from the obtained results that the proposed scheme provides better network connectivity at a low cost of memory occupation and communication overhead during the authentication and key establishment phases while improving its network resilience against attacks.